Developing and Implementing Performance Outcome Assessments: Evidentiary, Methodologic, and Operational Considerations. (January 2019) - Richardson, Elizabeth; Burnell, Jessica; Adams, Heather R.; Bohannon, Richard W.; Bush, Elizabeth Nicole; Campbell, Michelle; Chen, Wen Hung; Coons, Stephen Joel; Papadopoulos, Elektra; Reeve, Bryce R.; Rooks, Daniel; Daniel, Gregory
The use of performance outcome (PerfO) assessments to measure cognitive or physical function in drug trials presents several challenges for both sponsors and regulators, owing in part to a relative lack of scientific guidance on their development, implementation, and interpretation. In December 2016, the Duke-Margolis Center for Health Policy convened a 2-day workshop to explore the evidentiary, methodologic, and operational challenges associated with PerfO measures, and to identify potential paths to addressing these challenges. This paper presents both a summary of the discussion as well as additional input from a working group of experts from FDA, industry, academia, and public-private consortia. It is intended to advance the discussion around the development and use of PerfO measures to assess patient functioning in clinical trials intended to support registration of new treatments, and to highlight the key gaps in knowledge where additional research, collaboration, and discussion are needed.